Studi Kelayakan Water Pumped Energy Storage Sebagai Penyimpanan Energi PLTS Mandiri Pada Daerah Terisolir - Arif Priyohutomo; Dedet Candra Riawan; Soedibyo Soedibyo (Jurnal FORTECH, 2021)
Research and development on the implementation of renewable energy is growing rapidly, especially about photovoltaic (PV) and energy storage. Water pumped energy storage (WPES) is an alternative storage media in a standalone solar power system because of its longer technical life than chemical storage types, such as batteries. To assess the feasibility of WPES implementation as an energy storage in the standalone solar power plant system, the process of sizing the system components needs to be carried out by considering technical and economic aspects. This research will discuss the sizing process of standalone solar power system using WPES with closed loop reservoir systems and its economic analysis. The sizing process is carried out by the method of power balance, energy balance, and volume balance while economic viability is seen from the capital cost, O&M cost, and revenue from electrical energy absorbed by the load. In this study, the daily load profile with energy demand of 79 kWh and peak load of 4.36 kW. The analysis shows the need of 56 kWp PV system, 3800 m³reservoir capacity with 20m head. The calculation shows the technical efficiency of the system is 28.2%. From the economic analysis, the sistem’s payback period is 24 years, assuming the reservoir technical age is 50 years with net present value of Rp 2,072,823,731.86 and return of investment 105%.